Anaphylatoxin Receptors C3aR and C5aR1 Are Important Factors That Influence the Impact of Ethanol on the Adipose Secretome - McCullough, Rebecca L.; McMullen, Megan R.; Poulsen, Kyle L.; Kim, Adam; Medof, M. Edward; Nagy, Laura E. (Frontiers in Immunology, 2018)
Background & Aims: Chronic ethanol exposure results in inflammation in adipose tissue; this response is associated with activation of complement as well as the development of alcohol-related liver disease (ALD). Adipose communicates with other organs, including liver, via the release of soluble mediators, such as adipokines and cytokines, characterized as the “adipose secretome”. Here we investigated the role of the anaphaylatoxin receptors C3aR and C5aR1 in the development of adipose tissue inflammation and regulation of the adipose secretome in murine ALD (mALD). Methods: Wild-type C57BL/6 (WT), C3aR-/- and C5aR1-/- mice were fed Lieber-DeCarli ethanol diet for 25 days (6%v/v, 32%kcal) or isocaloric control diets; indicators of inflammation and injury were assessed in gonadal adipose tissue. The adipose secretome was characterized in isolated adipocytes and stromal vascular cells. Results: Ethanol feeding increased the expression of adipokines, chemokines and leukocyte markers in gonadal adipose tissue from WT mice; C3aR-/- were partially protected whileC5aR1-/- mice were completely protected. In contrast, induction of CYP2E1 and accumulation of TUNEL-positive cells in adipose in response to ethanol feeding was independent of genotype. Bone marrow chimeras, generated with WT and C5aR1-/- mice, revealed C5aR1 expression on non-myeloid cells, likely to be adipocytes, contributed to ethanol-induced adipose inflammation. Chronic ethanol feeding regulated both the quantity and distribution of adipokines secreted from adipocytes in a C5aR-dependent mechanism. In WT mice, chronic ethanol feeding induced a predominant release of pro-inflammatory adipokines from adipocytes, while the adipose secretome from C5aR1-/- mice was characterized by an anti-inflammatory/protective profile. Further, the cargo of adipocyte-derived extracellular vesicles (EVs) was distinct from the soluble secretome; in WT EVs, ethanol increased the abundance of pro-inflammatory mediators while EV cargo from C5aR1-/- adipocytes contained a greater diversity and more robust expression of adipokines. Conclusions: C3aR and C5aR1 are potent regulators of ethanol-induced adipose inflammation in mALD. C5aR1 modulated the impact of chronic ethanol on the content of the adipose secretome, as well as influencing the cargo of an extensive array of adipokines from adipocyte-derived EVs. Taken together, our data demonstrate that C5aR1 contributes to ethanol-mediated changes in the adipose secretome, likely contributing to intra-organ injury in ALD.